PERTIMBANGAN PENYIDIK MENGHENTIKAN PROSES HUKUM TERHADAP PELAKU TINDAK PIDANA KECELAKAAN LALU LINTAS YANG MENGAKIBATKAN ORANG LAIN MENINGGAL DUNIA DI KEPOLISIAN RESOR KOTA PEKANBARU - David Binsar Ari Mangasi; Dessy Artina; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Structuring or changes to the rules on the highway is absolute considering the current rules of Traffic and Road Transport has been deemed incompatible with the development and needs of society as set forth in the consideration of Law No. 22 of 2009 on Traffic and Road Transport. Cases that often experience pros and cons in the field of law is a case related to negligence. The neglect is usually done by most people ie in the case of traffic accidents, the accident until the death of the victim. A frequent form of violation in traffic on the highway is a traffic accident. For example, running beyond the specified speed limit then tire broke that resulted in the vehicle having an accident. Based on the description above, the authors are interested to examine the problem with the title: "Consideration of Investigators Stopping Legal Process Against Traffickers Traffic Accidents That Cause Others Died At Pekanbaru City Police". As for the formulation of the problem of the title is, first, how the process of solving the crime of traffic accidents that resulted in other people died in Pekanbaru Town Police Department? Secondly, what is the basis of consideration of the investigator to stop the legal process against the perpetrators of traffic accident at Pekanbaru Town Police Station? This type of research is empirical research, another term used is sociological legal research also called field research. This sociological law research is based on primary data. Primary data / basic data is data that can be directly from the community as the first source through through field research. Based on the results of the study authors concluded that The criminal acts of traffic accidents which resulted in the death of another person are common offenses which can not be stopped by legal process and result from negligence resulting in loss of life of others. The process of settling the criminal acts of traffic accidents which resulted in the death of others at Pekanbaru City Police Force in certain cases which have sufficient evidence to be solved through the judicial system. While for cases that have lack of evidence or cases due to negligence of victims, resolved through non-penal path that is by using the principle of ADR (Alternative Disupute Resolution)